Pengaruh Faktor Minat Nasabah Gadai Syariah dengn Gadai Konvensional pada PT. Pegadaian di Kota Mataram: The Influence of Customer Interest Factors in Sharia Pawning with Conventional Pawning on PT. Pawnshop in Mataram City - Maulana Ibahim; Fathurrahman; M. Habibullah Aminy (JURNAL EKONOMI, BISNIS DAN PARIWISATA, 2025)
Syariah and conventional pawnshops are non-bank financial services and are part of BUMN. People's interest in using pawnshop services is usually because they do not meet the requirements for loans from national or regional banks. People prefer to go to PT. Pawnshops are both syariah and conventional because they are considered faster in service, the disbursement process is fast and easy to reach by the public. This research uses a qualitative method with a case study approach. The research was conducted at Syariah Pawnshop Branches and Conventional Pawnshops in the Mataram City Area. The research sample was determined by purposive sampling and data collection by observation, interviews and documentation. Next, a data validity test was carried out. The results of this research show that people are more inclined to pawnshops because they are easier to reach, there are not many requirements, relatively fast service and fast disbursement of funds. Apart from that, products from syariah pawnshops prioritize syariah principles in accordance with Islamic teachings. Conventional pawnshops offer low interest promotions, longer tenors and better service quality. The researcher hopes that this research will be continued by future researchers as input for syariah and conventional pawnshops to improve the quality of services and financial service products that can compete with other financial service institutions.